The Mediating Role of E-Customer Satisfaction on PLN Mobile Application Users: An Analysis of the Influence of E-Service Quality and E-Trust on E-Customer Loyalty - Nugroho, Rafif; Wisnalmawati (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
This study aimed to analyze the influence of E-Service Quality and E-Trust on E-Customer Loyalty, with E-Customer Satisfaction as a mediating variable. This research was motivated by a phenomenon gap at PLN UP3 Yogyakarta, where massive digital promotions coexisted with persistent customer complaints, and a research gap concerning the inconsistent findings on the direct influence of E-Service Quality and E-Trust on E-Customer Loyalty. This study used a quantitative approach with a sample of 132 PLN Mobile users in the PLN UP3 Yogyakarta area, selected via purposive sampling. Primary data were collected via online questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The research findings showed that E-Service Quality and E-Trust had a non-significant effect on E-Customer Loyalty. Meanwhile, E-Service Quality and E-Trust had a significant impact on E-Customer Satisfaction, and (H5) E-Customer Satisfaction had a significant impact on E-Customer Loyalty. This finding proved that E-Customer Satisfaction acted as a full mediator (full mediation). The implication was that the loyalty of PLN Mobile users in Yogyakarta could not be built directly by service quality or trust, but must instead be achieved through customer satisfaction as the primary bridge.